Berberine Facilitates Extinction and Prevents the Return of Fear - Shihao Huang; Yu Zhou; Feilong Wu; Cuijie Shi; He Yan; Liangpei Chen; Chang Yang; Chang Yang; Yixiao Luo; Yixiao Luo (Frontiers Media S.A., 2022)
Exposure to a catastrophic event or intense stimulation can trigger fear memories, and the threatening memories persist even over a lifetime. Exposure therapy is based on extinction learning and is widely used to treat fear-related disorders, but its effect on remote fear memory is modest. Berberine, an isoquinoline alkaloid derived from Coptis chinensis or Berberis spp., has been recently reported to exert a diversity of pharmacological effects on the central nervous system, such as facilitating extinction of drug memory. Here, we explored the effect of berberine on extinction of fear memory using a classical contextual fear conditioning (CFC) paradigm, which is Pavlovian conditioning, can rapidly create fear memories related to contexts. Twenty-four hours or 30 days after CFC training, mice were subjected to context extinction (10 days) to extinguish their behaviors and treated with 12.5 or 25 mg/kg berberine intragastrically 1 or 6 h after each extinction session, followed by reinstatement and spontaneous recovery tests. The results showed that intragastric administration of 25 mg/kg berberine 1 h after extinction significantly promoted the extinction of recent and remote fear memories and prevented reinstatement and spontaneous recovery of extinguished fear in mice. These findings indicate that berberine combined with extinction training could serve as a promising novel avenue for the treatment of fear-related disorders.